Patterns of Principal Academic Supervision in the Digital Age at Madrasah Tsanawiyah - Ruhmi, Farah; Yuliana, Lia (AL-ISHLAH: Jurnal Pendidikan, 2025)
In the digital era, the role of school principals as academic supervisors has evolved significantly. This study examines the academic supervision patterns employed by the principal of MTSN 5 Sleman, focusing on how digital technology has transformed the supervision process. A qualitative method with a descriptive approach was used to explore the supervision practices. Data were collected from the principal of MTSN 5 Sleman and three senior teachers with substantial experience in academic supervision. Observations, interviews, and document analysis were conducted to gather insights. The findings reveal that the principal's academic supervision has become more effective and efficient through the integration of digital technology, particularly the madrasah principal's academic supervision narration application. This application streamlines supervision processes, optimizes resource usage, and enhances both learning quality and teacher competence. By leveraging this technology, the supervision approach has shifted to better meet contemporary educational needs. The transformation of academic supervision through digital tools demonstrates significant potential for improving educational outcomes. The study highlights the practical benefits of such innovations, including time savings and enhanced teacher performance. It also emphasizes the importance of strategic technology integration in academic supervision practices. The use of digital technology in academic supervision at MTSN 5 Sleman represents a pivotal step in modernizing education management. These findings offer valuable insights for education professionals and policymakers aiming to develop effective supervision strategies and embrace technological advancements in education.